SMALL AND MEDIUM-SIZED CITY POPULATIONS AS AN OBJECT OF SOCIOLOGICAL RESEARCH (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses the importance of the socio-cultural and urbanization process of small and medium-sized cities, the approaches and views of classical sociologists, modern foreign scholars, and scientists from CIS countries and Uzbekistan, who have conducted research in various areas of urbanization.